Implementation of Technology-Based Learning Through GSE (Google Suite Education) During the Covid-19 Pandemic in MI Miftahul Ulum Trimoharjo - Jami Ahmad Badawi; Sri Enggar Kencana Dewi (Latifah Pres, 2022)
The rapid development of information technology today has a positive impact on life, especially in the field of education. The most influential application in the field of education is the utilization of the internet network for the learning process. With the internet, information services can be accessed as a source of learning, learning media easily by learners. The streaming media is not only limited to letters and images, but is combined with graphics, animations, video, and audio simultaneously. Therefore, teachers are required to be more creative and innovative. Government assistance through GSE (Google Suite Education) is the right step to take advantage of the features contained in it as a support for the learning process. The application has various features such as google classroom and google meet that make it easier for teachers to carry out technology-based learning in the Covid-19 pandemic. This research uses qualitative methods in the form of a case study approach. The authors use interview data collection techniques, observations and documentation studies. The results of this study show that Google Suite Education makes it easier for teachers to do the learning process. GSE has many features that can be used to support the learning process, such as Google Classroom, Drive, Google meetings, video access and materials can be stored easily.